Hubungan antara gaya pembelajaran dengan pencapaian akademik pelajar: Kajian ke atas pelajar tingkatan empat - Zainab, Yaman (2008)
The aim of this study is to identify the relationship between learning style and academic achievement of a group of students. Two instruments, the adapted Learning Style Inventory (Dunn, Dunn and Price, 1978) and Perceptual Learning Style Preference Survey (Reid, 1984) were administered to a simple random sampling of 132 form four students of a boarding school in Kedah. The data were analyzed using SPSS version 12. Descriptive and inferential statistics were used to answer all the research questions. The results showed that there were significant differences in learning style between male and female students. Male students prefer auditory and group learning style, whereas female students prefer tactile, kinesthetic, visual and individual learning style. Results also indicated that male and female students are found to differ significantly to learning stimuli. Environmental and psychology stimuli affect female students and male students were more affected by emotional and physical stimuli. It was also found that there were significant differences in learning style between science stream and technical stream students. The results showed that technical students prefer tactile and group styles compare to science students. In term of learning stimuli, the results indicated that science students were less affected by all learning stimuli. Using ANOVA, results showed that there were only significant differences in tactile learning style and between female and male students. Results also indicated that only physical stimuli affected students in term of streaming. Pearson Correlation tests conducted to identify the relationship of independent and dependent variables. The results showed that there were weak relationship between group learning style and individual learning style with students' academic achievement. Based on the results, a number of suggestions are made to help teachers in their teaching by accommodating the students' preferred learning stimuli and learning styles to their teaching approaches